Keteraturan Antenatal Care (ANC) Terhadap Deteksi Resiko Tinggi Ibu Hamil - Rachmawati Ika Sukarsih (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: A high-risk pregnancy is a pregnancy that will cause greater danger and complications for both the mother and the fetus she contains during pregnancy, childbirth, or the postpartum period. This study aimed to determine the relationship between the regularity of ANC visits and o detection in pregnant women.Methods: The type of this research used was analytic, using a cross-sectional design. The population in this study were all high-risk pregnant women at BKIA RS Muhammadiyah Surabaya in June-July 2019. The sample of this study was some high-risk pregnant women with TM III at BKIA Hospital. Muhammadiyah Surabaya, in June-July 2019, had as many as 32 patients.Results: The characteristics of the regularity of ANC visits showed that most of the 16 respondents (50%) did ANC regularly. Most pregnant women were detected, as many as 24 people (75%). The Relationship of Regularity of ANC Visits Detection in Pregnant WomenConclusion: The mother's ability to detect early pregnancy danger signs is closely related to the characteristics of pregnant women and the support from the pregnant mother's environment. Collaborative strategies that are effective and efficient in increasing the ability of mothers to carry out early detection of danger signs of pregnancy through environmental support and ease of system access to information related to danger signs in pregnancy